PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP UPAYA PENGHINDARAN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERGABUNG DALAM INDEKS SAHAM SYARIAH INDONESIA TAHUN 2012-2015) - Ulwan Hawari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims to examine and analyze the influence of firm characteristic on tax avoidance. Firm characteristic is represented by size, leverage, capital intensity, inventory intensity. Tax avoidance in this research is measured by Effective Tax Rate (ETR) that is ratio of total income tax expense before total pre- tax accounting income. The sample that used in this study are secondary data of manufactured companies on Indeks Saham Syariah Indonesia (ISSI) on the Indonesia Stock Exchange (BEI) for the period of 2012-2015. Sample selection uses purposive sampling technique and hypothesis testing uses data panel multiple regression analysis with EViews 9. The result showed that capital intensity and inventory intensity have a negative effect and significant in tax avoidance. However, size and leverage did not influence the tax avoidance. Keywords: Tax avoidance, size, leverage, capital intensity, inventory intensity